Effects of sudden failure of shoring elements in concrete building structures under construction. (1st October 2018) - Buitrago, Manuel; Sagaseta, Juan; Adam, Jose M.
Graphical abstract: Highlights: FE models were carried out of a three-storey RC building and its shoring system. The failure scenarios considered followed the notional member removal approach. Four local failure scenarios of the most heavily loaded shores were considered. The structure-shoring system was able to develop alternative load paths. Design recommendations are given based on the results from these analyses. Abstract: The most frequently used technique to construct reinforced concrete (RC) building structures is the shoring or propping of successive floors, in which the slabs are supported by the shores until the concrete acquires sufficient strength. A significant number of structural failures have been reported during construction in recent years leading in some cases to the progressive collapse of the whole structure. The collapse often starts with the local failure of a single element which could be due to errors in design or construction and/or due to accidental events. Although this is a well-recognized problem, studies on the effects of local failure in the shoring elements on the integrity of the shoring-structure system have not been carried out in the past. In this work advanced numerical finite element models were carried out of a three-storey RC building and its shoring system. Four scenarios of local failure were considered: sudden removal of a (1) shore, (2) joist and (3) complete shore line; and (4) incorrect selection of shores. The results indicated that the structure-shoring system was able to develop alternative load paths without dynamic amplification effects due to the large stiffness and redundancy of the system without compromising the integrity of the structure but leading to significant damage in the concrete slabs. Design recommendations are also given based on the results from this study, which pretend to be the first study to focus on the structural response and damage of a building structure under construction after the sudden failure of one or more shores.